Exploring capabilities of international technology transfer intermediaries between emerging and developed countries - Palaco, Ileana; Kim, Suk Kyoung; Park, Min Jae; Rho, Jae Jeung (Journal of Technology Transfer, 2022)
We report which capabilities are essential to a successful demand-driven inter-organizational international technology transfer (ITT) when a business deal involves an emerging country recipient and a developed country source. Using a mixed-methods approach, the study collected opinions from 74 experts from 12 countries on technology transfer and diffusion, innovation systems and networks, and knowledge-intensive business services. In a preliminary attempt to identify which skills are critical, we present the perspective of emerging countries’ stakeholders. The suggested 28 critical capabilities can be used as an input for further empirical analysis. The conceptual framework can be applied to assess an intermediary’s performance for a given ITT project in which the demand arises from an emerging-country stakeholder.
Keywords: Conceptual frameworks; Developed countries; Emerging countries; Empirical analysis; Innovation system; Inter-organizational; International technology transfers; Knowledge intensive business services; Capabilities; Demand-driven; Emerging countries; Innovation intermediaries; International technology transfer